Democratic Institutions Without Democratic Content?-New Regionalism and Democratic Backsliding in Regional Reforms in Sweden - Johansson, Jörgen; Rönnblom, Malin; Öjehag-Pettersson, Andreas (Frontiers in Political Science, 2021)
The aim of the article is to examine trends of democratic backsliding associated with the reform work on regional institutions and policies in Sweden, and where democratic backsliding is conceptualized in a more implicit manner compared to conventional understandings. The article highlights a missing aspect in the research on democratic backsliding on how even well-thought-out reforms on strengthening democratic institutions risks to fail. The Swedish reforms was completed in 2019 after 30 years of reform efforts. A new political arena has been created when the former county councils are transformed to be called regions. The regions have been assigned responsibility for both health care and regional development planning. The reforms had two key policy objectives; (1) to contribute to economic growth and (2) strengthen democratic values. The research problem focuses on the relations between regional democracy and neo-regionalism. The reform processes are analyzed through theoretical lenses inspired by regionalist thinking, theories of regional democracy, and governmentality. The results highlight how the governing rationalities in the regional reform processes have changed during the period between 1990 and 2020. The original conception of creating a mini-version of a liberal and representative democracy have turn into a form of democratic backsliding privileging economic goals. The economic rationalities that permeate the political sphere today close the space for articulated different interests and opinions – a dimension that we argue is crucial for a democratic society. We draw two main conclusions: First that the neoliberal aspect of governing is missing in the analysis of democracy at the regional level, resulting in a descriptive discussion of democracy as well as ignoring the effects of the particularly strong emphasis on economic growth. Secondly, that there is a lack of a discussion on democracy that takes the regional level into account, i.e that the sub-national level should be regarded and thus discussed as a distinctive level of democracy.